Peran Kepemimpinan Kepala Sekolah dalam Pengelolaan Anggaran Pendidikan: The Role of Principal Leadership in Managing the Education Budget - Pangestu, Prayogo; Gandasacita, Ilham; Maftuhah, Maftuhah (Thawalib: Jurnal Kependidikan Islam, 2024)
Management at Darul Huda Integrated Private Junior High School focuses on budget management that relies on the School Operational Assistance Fund and external donations. The aim is to assess the role of the principal in the effectiveness of budget management and its impact on the use of those funds. The research was conducted using mixed methods, with data collection through interviews, observations, documentation, and questionnaires. Data processing involved condensation, presentation, verification, and ended with a t-test. The results show: (1) The principal acts as an educational manager by prioritizing the school's needs and involving staff in planning. As an educational entrepreneur, the principal ensures budget transparency and seeks alternative funding sources. As a supervisor, the principal conducts periodic evaluations of budget usage. (2) The principal's role as a manager, educational entrepreneur, and financial supervisor significantly impacts the management of educational budgets. Conclusion: The principal has maximized financial management to meet the school's needs.